Asa Gray papers - Gray, Asa, 1810-1888.
Chiefly letters relating to botanical matters from Gray and his wife, Jane Loring Gray, to botanist Elizabeth Carrington Morris and her sister, naturalist Margaretta Hare Morris. Also includes letters to the Morris sisters from Louis Agassiz, Samuel Stehman Halderman, Thaddeus William Harris, and Benjamin Silliman. Also included are two articles possibily written by entomologist Thomas Say for the journal of the Academy of Natural Sciences of Philadelphia.
Botanist and professor of natural history at Harvard University.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Agassiz, Louis, -- 1807-1873 -- Correspondence; Gray, Jane Loring, -- 1821-1909 -- Correspondence; Haldeman, Samuel Stehman, -- 1812-1880 -- Correspondence; Harris, Thaddeus William, -- 1795-1856 -- Correspondence; Morris, Elizabeth Carrington, -- 1775-1865 -- Correspondence; Morris, Margaretta Hare, -- 1797-1867 -- Correspondence; Say, Thomas, -- 1787-1834.; Silliman, Benjamin, -- 1816-1885 -- Correspondence; Academy of Natural Sciences of Philadelphia; Harvard University -- Faculty; Botany -- Study and teaching; Entomology; Natural history; Botanists; Educators